Immune Characterization of Ovarian Cancer Reveals New Cell Subtypes With Different Prognoses, Immune Risks, and Molecular Mechanisms - Cong, Shanshan; Guo, Qiuyan; Cheng, Yan; He, Yanan; Zhao, Xibo; Kong, Congcong; Ning, Shangwei; Zhang, Guangmei (Frontiers in Cell and Developmental Biology, 2020)
Ovarian cancer (OV) is a considerable threat to the health of women due to its complex mechanisms and atypical symptoms. Various currently available treatments fail to substantially increase the survival rate of OV patients. The tumor microenvironment (TME) is gaining attention due to its role in tumorigenesis and tumor progression. This study mainly investigated the immune characteristics of OV by CIBERSORT and MCP-counter. We reclassified OV into four TME cell subtypes with different prognoses and evaluated the infiltration of the cells in each subtype. The immune risk of diverse subtypes was evaluated based on the immunoscore calculated by Cox regression analysis. The molecular mechanisms and hallmark pathways of the four subtypes were analyzed. The results indicate that the immune procancer cell subtype is associated with the worst prognosis, closely related to the high immune risk group, and characterized by low expression of checkpoints and MHC class I and II molecules, high expression of hypoxia-related genes, high enrichment of the EMT and hypoxia pathways, and low enrichment of the DNA repair and interferon α response pathways. This study contributes to the investigation of immune mechanisms and identifies more effective targets for immunotherapy of OV.